Improved Nocturnal Glycaemia and Reduced Insulin Use Following Clinical Exercise Trial Participation in Individuals With Type 1 Diabetes - McCarthy, Olivia; Deere, Rachel; Eckstein, Max L.; Pitt, Jason; Wellman, Ben; Bain, Stephen C.; Moser, Othmar; Bracken, Richard M. (Frontiers in Public Health, 2021)
Aim: To explore the influence of clinical exercise trial participation on glycaemic and insulin therapy outcomes in adults with type 1 diabetes (T1D). Research Design and Methods; This study involved a secondary analysis of metrics collected from sixteen individuals with T1D who completed a randomised clinical trial consisting of 23-hour inpatient phases with a 45-minute evening bout of moderate intensity continuous exercise. Participants were switched from their usual basal-bolus therapy to ultra-long acting insulin degludec and rapid acting insulin aspart as well as provided with unblinded interstitial flash-glucose monitoring systems. To assess the impact of clinical trial participation, weekly data obtained at the screening visit (pre-study involvement) were compared against those collated on the last experimental visit (post-study involvement). Interstitial glucose [iG] data were split into distinct glycaemic ranges and stratified into day (06:00-23:59) and night (00:00-05:59) time periods. A p value of ≤0.05 was accepted for significance. Results; Following study completion, there were significant decreases in both the mean nocturnal iG concentration (∆-0.9±4.5 mmol.L-1, p<0.001) and the time spent in severe hyperglycaemia (∆-7.2±9.8%, p=0.028) during the night-time period. The total daily (∆-7.3±8.4 IU, p=0.003) and basal only (∆-2.3±3.8 IU, p=0.033) insulin dose requirements were reduced over the course of study involvement. Conclusions; The improvements in nocturnal glycaemia and reduced insulin use observed in this study highlight the potential wider, clinically relevant benefits associated with clinical trial participation in individuals with T1D. Recognition of these outcomes may help encourage volunteers to partake in clinical research opportunities for improved diabetes-related health outcomes.